Från restbiomassa till protein: En studie om filamentösa svampar - Bergstedt, William; Björnelf, Stina; Johansson, Cecilia; Rydberg, Cecilia (My University, 2023)
One of today’s greatest challenge is producing enough nutritious food for the growing population of the world in a sustainable way. One solution could be the increased use of residual biomass. Forestry and agriculture generate an estimated 140 gigatons of residual biomass annually globally. Some of these residual streams can be valorized by filamentous fungi, which convert residual biomass into proteins to produce food and animal feed. This Bachelor thesis aimed to contribute to a more sustainable production of food by improving the growth of filamentous fungi on Spent Sulfur Liquor (SSL) with two methods of Classical Strain Improvement (CSI) and investigated in whether fungi can grow on other waste streams. Eight proprietary strains (mutants of CirkuleinTM) and Trichoderma reesei, Aspergillus niger, Aspergillus nidulans and Myceliophthora thermophila were screened. The original and mutated fungi were screened on different liquid media to determine the strains most adapted to each media. The best strains, ranked by growth rate, were grown in shake flasks and their dry biomass was measured. Fungi were also grown on solid media in petri dishes. Methods used for strain development are Adaptive Laboratory Evolution (ALE) and UV mutagenesis, with the ambition to mutate strains with a higher growth rate that can be used in large-scale industries. The screening of the strains resulted in six strains being chosen for fermentation in shake flasks. The largest growth, in terms of dry weight, was obtained from the strains grown on SSL. The ALE showed a slight improvement in growth rate for one CirkuleinTM-strain while another remained unchanged. The UV-mutagenesis resulted in a survival rate of 1-3% and one of the mutated colonies showed an improved growth rate. The other replicates generally showed a lower growth rate than the control groups. From the screening on liquid media, it can be concluded that high-throughput screening is an effective first thinning of available strains. However, fermentation in shake flasks is necessary to get a reliable result since it ensures that the fungi are growing on the medium and not on the agar, for example. Though the fungi grew best on SSL they also grew on the other side streams tested and it is therefore of interest to continue investigating those. The fungi grew on two of the solid media, but their growth was inhibited on the coffee grounds. UV mutagenesis is a method that can produce improved strains, though a low survival rate is imperative to see change in a small sample size. ALE also procured improved strains, however, some of the developed strains obtained an unchanged growth rate. For both of these methods, further rounds of treatment would be necessary to obtain more efficient strains. Furthermore, the concentrations of the SSL used in ALE should be assessed in further studies to optimize the strain development